precalculus

posted by .

write the expression below as a single logarithm show work.

ln(x-7/x^2+12x+36)-ln(x^2-49/x+6)

• precalculus -

first
x^2+12x+36 = (x+6)(x+6)
so

ln of

(x-7)(x+6)
=====================
(x+6)(x+6)(x+7)(x-7)

ln of

1
=====================
(x+6)(x+1)

= ln 1 - ln(x^2 +7x + 6)
but ln 1 = 0
so
- ln (x^2 + 7 x + 6)

Similar Questions

1. Precalculus

1. Write the given expression as a single logarithm. log(70x)+log(10y)-2 2. Write the given expression as a single logarithm. ln7e/(square root 2x)-ln(square root 2ex) 3. Write the given expression as a single logarithm. -2Ln(x)+Ln(4y)-Ln(5z)
2. Precalculus

Write the given expression as a single logarithm. log(70x)+log(10y)-2
3. Precalculus

1. Write the given expression as a single logarithm. log(70x)+log(10y)-2 2. Simplify the expression. (Do not use mixed numbers in your answer.) (5x^7/8)(2y^4/6)(x^9/8)(4y^-2/6) 3. Write the given expression as a single logarithm. -2Ln(x)+Ln(4y)-Ln(5z) …
4. Math - Write expression as single logarithm

Write the expression below as a single logarithm. Please show all of your work. ln((x^2 – 1)/(x^2 – 6x + 8)) – ln((x+1)/(x+2))
5. pre calculous

use the properties of logarithms to write the expression as a sum or difference of logarithms or multiples of logarithms. show your work ln x^2/y^3 Assuming x,y AND z are positive use properties of logariths to write the expression …
6. pre calculus

Write the expression below as a single logarithm. 2in(x+4)-in((x^(2)+x-12)/(x))
7. pre calculus

Write the expression below as a single logarithm. Need to know how to work this! ln(x-5/x^2 - 1) - ln (x^2 - 2x -15/x + 1)
8. college algebra

write the expression as a single logarithm In(x/x-2)+In(x+2/x)-In(x^2-4) Please show work
9. ALGEBRA

CONTACT THE EXPRESSIONS.THAT IS USE THE PROPERTIES OF LOGARITHM TO WRITE EACH EXPRESSION AS A SINGLE LOGARITHM WITH A COEFFICIENT OF 1. In 3-2 in 9 + 18 in 3-2 in (9+6) in 3-2 (in 4 + in 8)
10. PreCalculus - Need help, due tonight

1. Rewrite the expression 1/2ln(x – 6) + 3ln(x +1) as a single logarithm. 2. Rewrite the expression 1/3[ln x – 2ln(1 – x)] as a single logarithm.

More Similar Questions